Efficient use of natural resources and modern coal processing technologies (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
According to the categories of coal mined in the coal mines of Kyrgyzstan, brown and hard coals are characterized by the degree of metamorphism. Coal processing technologies, production methods, products developed with the participation of the authors: chopped firewood, semi-coke (charcoal) and others. Experimental laboratory for the preparation of components for the production of humated organomineral fertilizers (GOM) based on oxidized brown coal: washing of humic substances with alkali from oxidized brown coal, production of vermicompost (humus) using Californian red earthworm, separation of glauconite from natural mineral. results and data are presented in tables. Conclusions are prepared on the basis of scientific research, recommendations are presented in the final section.
Keywords: coal, brown coal, coal deposits, oxidized brown coal, humus, humated organomineral fertilizers, vermicompost, glauconite